Optimizing reforestation: Investigating the efficacy of 3D printed biomimicry seed pod shapes in enhancing seed dispersal - Jeffri, Muhammad Syazani Irfan; Yu, Cohen Riley Ong; Marzuki, Omar Faruqi; Teo, Ellie Yi Lih; Johan, Norzaliza (Journal of Forests, 2025)
This paper addresses the crucial challenge in reforestation of effectively distributing seeds over large and often inaccessible areas. Traditional methods, limited in cost, reach, and efficiency, are contrasted with innovative solutions that leverage 3D printing technology and biomimicry principles. The research aims to develop seed pods that emulate natural seed dispersal mechanisms, offering a potential revolution in reforestation practices. These 3D printed seed pods, inspired by natural dispersers like gliding maple seeds and parachuting dandelion seeds, are designed to optimize travel distance, thus maximizing seed dispersal. Methodologically, the study employs SolidWorks and PrusaSlicer for designing, with drop tests conducted from a three-level building to evaluate the travel distance performance of various seed pod types. The results indicate significant variability in travel and bounce characteristics based on seed pod design, highlighting the design with wing-like features as particularly effective in achieving longer travel distances. These findings emphasize the crucial role of shape design in seed pod performance, presenting a novel approach to enhance seed dispersal efficiency in reforestation efforts. The research contributes not only to environmental science and technological ingenuity but also serves as a first step for future interdisciplinary studies. For environmental scientists, ecologists, and practitioners involved in reforestation interventions, the findings have important implications for sustainable, cost-effective interventions with the potential to improve livelihoods, support biodiversity, and aid climate regulation. Future research directions include trials in field situations across varying ecological contexts, investigation of environmentally friendly materials, and expansion of biomimetic designs for greater efficacy in seed dispersing.